Anies Baswedan's Political Communication: Ferdinand De Saussure's Semiotic Analysis of the Event Using Anies Ambon - Sofiyatul Laily Badriyah; Khomsiyatul Mukarromah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The 2024 Indonesian presidential election is a crucial moment in political communication, with each candidate employing various campaign tactics to enhance their reputation and win public favor. The "Desak Anies Ambon" program is one such campaign that utilizes direct communication between the public and the candidate as a means to express goals and construct political meaning. This study employs a semiotic approach to examine Anies Baswedan's political communication style and uncovers how meaning is constructed in the "Desak Anies Ambon" program. This research employed an interpretive qualitative approach. Observations of the "Desak Anies Ambon" program uploaded to the official YouTube channel were used to collect data. Ferdinand de Saussure's semiotic theory, which emphasizes the relationship between the signifier and the signified, was then used to study it. The findings indicate that a dialogic, relaxed, and responsive communication style was employed, fostering a sense of community, transparency, and inclusive leadership. Political messages were reinforced and made more understandable to the audience through the use of straightforward language, direct communication, and responsiveness to local issues. Consequently, this program's communication approach shaped the political image through a system of indicators interpreted by the public, while also serving as a campaign medium.